2011
DOI: 10.2118/0711-0022-jpt
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Optic Sensing Technology Providing Well, Reservoir Information - Anyplace, Anytime

Abstract: Technology Update Fiber-optic sensing is known in the oil and gas industry as a technology that allows continuous temperature profiling along entire well paths. However, surveillance applications focusing solely on temperature measurements are limited to recovery processes with a clear, unambiguous thermal signature. This has prevented fiber-optic sensing from becoming a widely deployed technology in oil and gas production. However, we are now witnessing a confluence of novel fiber-optic technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Indeed, a FOC is usually made of several single and multi-mode fibers that can be used for a variety of applications. This potential has been evidenced and leveraged by the oil and gas industry for around one decade (Koelman et al, 2012;Koelman, 2011;Van Der Horst et al, 2013).…”
Section: Logging and Monitoring Capabilities Of Das Along Wellmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a FOC is usually made of several single and multi-mode fibers that can be used for a variety of applications. This potential has been evidenced and leveraged by the oil and gas industry for around one decade (Koelman et al, 2012;Koelman, 2011;Van Der Horst et al, 2013).…”
Section: Logging and Monitoring Capabilities Of Das Along Wellmentioning
confidence: 99%
“…Depending on the deployment design, which remains challenging for deep (hot) boreholes, this can provide information on temperature profiles, well completion integrity, in-and out-flow zones of the geothermal fluid, induced seismicity, etc. (Koelman, 2011;Koelman et al, 2012;Van Der Horst et al, 2013). For seismic monitoring, DAS along the borehole allows sensors to be positioned much closer to the reservoir than surface seismometers, thus closer to the potential seismicity.…”
Section: Introductionmentioning
confidence: 99%
“…It leverages optical fibers to deliver repeatable in-situ observation of changes in temperature, strain and/or strain-rate. DOFS applications demonstrated that it could provide insight into, e.g., in-flow and out-flow zones, fluid flow rates, well integrity, and induced seismicity [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%